STAT6 and IL‐10 are required for the anti‐arthritic effects of Schistosoma mansoni via different mechanisms. (15th October 2018) - Osada, Y.; Horie, Y.; Nakae, S.; Sudo, K.; Kanazawa, T.
Summary: To investigate possible roles of T helper type 2 (Th2) cytokines in the anti‐arthritic effects of a blood fluke, Schistosoma mansoni (Sm), for mouse collagen‐induced arthritis (CIA), wild‐type (WT), signal transducer and activator of transcription 6 (STAT6) knock‐out (KO) and interleukin (IL)‐10 KO mice were infected with Sm. Three weeks after infection, the mice were immunized with bovine type II collagen (IIC). Arthritis severity was monitored by scoring, measurement of paw thickness and the presence of ankylosis. Serum anti‐IIC IgG levels, splenic cytokine production and cytokine gene expression in the popliteal lymph nodes (PLNs) were measured and compared among WT and gene‐KO mice. Consistent with our previous findings, Sm infection reduced the arthritis severity in WT mice. Splenic production of IL‐17A and tumor necrosis factor (TNF)‐α was reduced by the infection. In contrast, Sm infection markedly exacerbated CIA in STAT6 KO mice. In the KO mice, IL‐17A production was increased by the infection. Conversely, Sm infection did not affect the exacerbated arthritis in IL‐10 KO mice, although IL‐17A production was reduced by the helminth. Our results suggest that signaling via STAT6 (presumably IL‐4 and/or IL‐13) and IL‐10 is required for the suppression of CIA by Sm infection, but through different mechanisms. STAT6 was essential for helminth‐induced reduction of IL‐17A, whereas regulation of the basal arthritis severity by IL‐10 was needed in order for it to be sufficiently suppressed by the helminth. Abstract : Schistosoma mansoni infection reduces severity of collagen‐induced arthritis in mice. STAT6‐ mediated signaling and IL‐10 are essential for the anti‐arthritic effects of the helminth.